Ironic effect on emotional response and attitude: moderating role of incongruity degree. - Gu, Junwen (2020)
This dissertation probed the relationship between degree of incongruity, emotional response and attitude in an advertising context based on Mandler’s (1982) schema incongruity theory.The schema incongruity theory has been studied by psychologists to explain how it evokes people’s extra psychological efforts to produce satisfaction feelings after finishing the resolution by reconciling the inconsistency between the incongruent message they are exposured and the original schema. This theory is also contributed to the field of advertising research as it could assist advertisers to forecast how consumers would utilize the schema incongruity to process and assess their advertisings and brands. Additionally, as three components of affective factors in advertising context, attitude towards the advertising (Aad), attitude towards the brand (Ab) plus emotional response are crucial determinants for advertising success. However, the measurement of emotional response in previous schema incongruity researches was always twisted its role by adopting the insufficient cognitive measures to evaluate emotions. Typical problems such as wrongly recognize the conception of “affect” or “attitude” as emotional response, fail to distinct respondents’ emotional responses changes generated by different levels of incongruity or only measure the comparison between the congruent and extremely incongruent situation neglecting the role of moderate incongruity degree. Thus, this dissertation would focus on the advertising effectiveness research by moderating the role of incongruity degree(congruity, moderate incongruity and extremely incongruity) which adopts the quantitative method. The purpose of this study is to find out the effects of different advertising incongruity degree on people’s attitudes and emotional responses. Secondly, this dissertation would also try to answer the research question as how consumers’ emotional response and attitude would be affected in these three degree levels and explore the relationship among the dependent variables. The literature review offered a solid theoretical premise related to ironic advertising, schema incongruity and emotional response with a summarization of most main authors and the literature correlated to the research topic. The contribution of this dissertation is to provide deeper insights into the differences of ironic advertising on consumers’ attitudes and emotional responses through adding the moderating variable of the incongruity degree, either support or refuse the hypotheses that moderate incongruity (ironic) advertising would lead to greater emotional response and attitude towards the advertising and brand. In order to clarify and examine these theories and findings, a MANOVA test and between-subject analysis were designed to explore whether there was a significant difference among means of dependent variables in three incongruity degrees. In addition, Tukey post-hoc tests were also included to find out significant differences between subgroups of three incongruity levels. Finally, a Pearson’s correlation test was adapted so as to identify the relationship between each dependent variable. The advertising stimuli were created and pretested to ensure that the established incongruity level (congruity, moderate incongruity and extremely incongruity) could be understood and accepted by the majority of participants. The independent variable was the degree of incongruity. The dependent variables were the emotional response, attitude towards the ad and attitude towards the brand. It was proved that the degree of incongruity had an influence on people’s attitudes towards the ads, brands and emotional response, which ads with moderate incongruity level performed best compared to other two incongruity degrees. Furthermore, there was a strong positive relationship between pleasure, dominance, Aad, Ab, however, there was no direct and positive relationship between dominance/arousal and pleasure/arousal, especially when the incongruity degree is too high. Advertisers will benefit from the result as they will know how to optimize consumers’ emotional response and attitude towards the ads and brands with the most appropriate situation to apply ironic message as well as how to avoid the pitfalls that only consider how to increase people's arousal or attention to the ads but ignore the remaining affective elements.